(untitled) (REMUNOM, 2025)
This study analyzes the transformations of the Ego Ideal in contemporary times in the light of psychoanalysis, focusing on the impact of social media, the decline of the symbolic ideal, and the demands of jouissance. The investigation revisits Freud’s formulation of the Ego Ideal as a psychic instance that guides the ego and regulates the subject’s desire, articulating it with Lacanian contributions, which highlight the constitutive lack of this instance and its function in the economy of desire. It is observed that, in the current context, the centrality of social media favors the predominance of the imaginary register, sustained by identifications with idealized images, whose validation by the gaze of the Other intensifies the subject’s alienation from their own desire. Simultaneously, the weakening of traditional symbolic references undermines the mechanisms that regulate desire, establishing a logic of immediate jouissance, consistent with the dynamics of capitalist discourse. This process affects both individual subjectivity and social bonds, generating a crisis of meaning marked by the fragility of symbolic resources and the predominance of the imperative of unlimited satisfaction. Of qualitative and exploratory character, the study uses psychoanalytic theory as a framework for analysis and critical reflection, concluding that psychoanalysis, by emphasizing the elaboration of desire and the acknowledgment of lack, provides theoretical and clinical tools to understand contemporary challenges of subjectivity, fostering the reconstruction of symbolic bonds and supporting an ethics that counters the logic of unlimited jouissance.